Putting Plant Genetic Diversity and Variability at Work for Breeding: Hybrid Rice Suitability in West Africa - El-Namaky, R.; Coulibaly, M.M.B.; Alhassan, M.; Traoré, K.; Nwilene, F.; Dieng, I.; Ortíz, R.; Manneh, B. (MDPI, 2017)
Rice is a staple food in West Africa, where its demand keeps increasing due to population growth. Hence, there is an urgent need to identify high yielding rice cultivars that fulfill this demand locally. Rice hybrids are already known to significantly increase productivity. This study evaluated the potential of Asian hybrids with good adaptability to irrigated and rainfed lowland rice areas in Mali, Nigeria, and Senegal. There were 169 hybrids from China included in trials at target sites during 2009 and 2010. The genotype × environment interaction was highly significant (p < 0.0001) for grain yield indicating that the hybrids’ and their respective cultivar checks’ performance differed across locations. Two hybrids had the highest grain yield during 2010 in Mali, while in Nigeria, four hybrids in 2009 and one hybrid in 2010 had higher grain yield and matured earlier than the best local cultivar. The milling recovery, grain shape and cooking features of most hybrids had the quality preferred by West African consumers. Most of the hybrids were, however, susceptible to African rice gall midge (AfRGM) and Rice Yellow Mottle Virus (RMYV) isolate Ng40. About 60% of these hybrids were resistant to blast. Hybrids need to incorporate host plant resistant for AfRGM and RYMV to be grown in West Africa.